Good governance in administrative services at village level: Case study of Diat village, Bukal district, Buol regency - Saleh Al Hamid; Fitriyani R. Laundu (Tamalanrea: Journal of Government and Development (JGD), 2025)
This study uses a descriptive qualitative method approach to analyze the implementation of Good Governance principles in administrative services at the Diat Village level, Bukal District, Buol Regency. Data were collected through in-depth interviews, observations, documentation, and field notes that rely on information from informants and secondary sources such as related books and articles. Data analysis was carried out in three stages: data reduction, data presentation, and drawing conclusions. The main focus of this study is the indicators of responsiveness, efficiency, and effectiveness in village administrative services. The results of the study indicate that the implementation of the responsiveness principle in public services in Diat Village has not been maximized, due to the low responsiveness of officers in responding to community needs. In addition, the implementation of the efficiency and effectiveness principles has also not been optimal, with obstacles such as the long distance between the officer's house and the slow process of processing signatures. Although the Village Secretary tries to provide fast service, the absence of a village office as a service center hinders efficiency and extends the time for completing administration. This study provides important insights into the challenges in implementing Good Governance principles at the village level and the need for improvements in the aspects of responsiveness, efficiency, and effectiveness of public services.